Au/TiO2 catalysts promoted with Fe and Mg for n-octanol oxidation under mild conditions; Catalysis Today; Vol. 278, Pt. 1 : Selectivity in Oxidation: Key to new resources valorization (ISO ’15) - Kotolevich Yu. I. Yuliya; Kolobova E. N. Ekaterina Nikolaevna; Mamontov G. V. Grigory Vladimirovich; Khramov E. A. Evgeny; Cabrera Ortega J. E. Jesus Efren; Tiznado H. L. Hugo; Farias M. H. Mario; Bogdanchikova N. E. Nina Evgenjevna; Zubavichus Ya. V. Yan Vitautasovich; Mota-Morales J. D. Josue; Cortes C. V. Corberan; Zanella R. A. Rodolfo; et al. (2016, 2016)
Title screen